Interaction of aggregated native and mutant IgE receptors with the cellular skeleton. - Mao, S Y (1992)
When aggregated, cell surface proteins become resistant to solubilization by detergents, presumably because of aggregation-induced or -stabilized interactions between the membrane protein and the cytoskeleton or plasma membrane skeleton. We genetically engineered variants of the tetrameric high-affinity receptor for IgE (Fc epsilon RI) to identify a site on its alpha, beta, or gamma chains that mediates such putative interactions. Using flow cytofluorometry, we studied rat basophilic leukemia cells, transiently transfected COS cells, and stably transfected P815 cells bearing wild-type and mutated receptors. We observed that (i) solubilization was markedly dependent on the degree of aggregation, the extent varying somewhat with the cell type and, particularly at lower levels of aggregation, with the time after addition of detergent; (ii) truncation of no single cytoplasmic domain of the alpha, beta, or gamma chains ablated the insolubilization effect; and (iii) incomplete receptors were also efficiently insolubilized by aggregation. Thus receptors consisting only of alpha and gamma chains, a "receptor" consisting of only the ectodomain of the alpha chain attached to the plasma membrane by a glycosyl-phosphatidyl inositol anchor, and "receptors" consisting only of minimally modified gamma chains were resistant to solubilization after aggregation. We conclude that no unique subunit or domain of Fc epsilon RI mediates the insolubilization phenomenon. Our results support a model in which the bridging of membrane proteins leads to their becoming nonspecifically enmeshed in a network of membrane skeletal proteins on either the outside and/or the inside of the membrane so that dissolution of the lipid bilayer becomes irrelevant.